Persistence of Minimal Residual Disease Assessed by Multi-Parameter Flow Cytometry is Highly Prognostic in Younger Patients with Acute Myeloid Leukemia - Ravandi, Farhad (Cancer, 2016)
BACKGROUND: Predicting outcome in patients with acute myeloid leukemia (AML) using pre-treatment predictors has been the cornerstone of management. Post-treatment prognostic factors are increasingly evaluated. METHODS: Among 280 younger patients treated with intermediate dose cytarabine (total of ≥ 5 g/m(2)) and idarubicin based induction chemotherapy who achieved remission, 186 were assessed for MRD using an 8-color multi-parameter flow cytometry (MFC) panel performed on bone marrow specimens, with a sensitivity of 0.1% or higher. RESULTS: 166 patients had available samples at 1-2 months post induction at the time of achieving complete remission (CR) and 79% became negative for MRD, with MRD-negative status associated with improvement in relapse free survival (RFS) (p= 0.0002) and overall survival (OS) (p= 0.0002). 116 were evaluated for MRD status during consolidation and 86% were negative with a MRD-negative status associated with a significant improvement in RFS (p<0.0001) and OS (p<0.0001). 69 patients were evaluated for MRD status after completion of all therapy and 84% were negative with a MRD-negative status associated with improvement in RFS (P<0.0001) and OS (P<0.0001). On multivariate analysis including age, cytogenetics, achieving CR vs. CRp/CRi, and MRD, achieving MRD-negative status was the most important independent predictor of RFS and OS at response (p=0.008 and p=0.0008, respectively), during consolidation (p<0.0001 for both), or at completion of therapy (p<0.0001 and p=0.002). CONCLUSION: Achieving MRD-negative status by MFC is associated with a highly significant improvement in the outcome of younger patients with AML receiving ara-C plus idarubicin-based induction and consolidation regimens.